Enrichment of Rice Flour with Almond Bagasse Powder: The Impact on the Physicochemical and Functional Properties of Gluten-Free Bread - Stevens Duarte; Janaina Sánchez-García; Joanna Harasym; Noelia Betoret (Foods, 2025)
Almond bagasse, a by-product of almond milk production, is rich in fibre, protein, polyunsaturated fatty acids, and bioactive compounds. Its incorporation into food products provides a sustainable approach to reducing food waste while improving nutritional quality. This study explored the impact of enriching rice flour with almond bagasse powders—either hot air-dried (HAD60) or lyophilised (LYO)—at substitution levels of 5%, 10%, 15%, 20%, 25%, and 30% (w/w), to assess effects on gluten-free bread quality. The resulting flour blends were analysed for their physicochemical, techno-functional, rheological, and antioxidant properties. Gluten-free breads were then prepared using these blends and evaluated fresh and after seven days of refrigerated storage. The addition of almond bagasse powders reduced moisture and water absorption capacities, while also darkening the bread colour, particularly in HAD60, due to browning from thermal drying. The LYO powder led to softer bread by disrupting the starch structure more than HAD60. All breads hardened after storage due to starch retrogradation. The incorporation of almond bagasse powder reduced the pasting behaviour—particularly at substitution levels of ≥ 25%—as well as the viscoelastic moduli of the flour blends, due to fibre competing for water and thereby limiting starch gelatinisation. Antioxidant capacity was significantly enhanced in HAD60 breads, particularly in the crust and at higher substitution levels, due to Maillard reactions. Furthermore, antioxidant degradation over time was less pronounced in formulations with higher substitution levels, with HAD60 proving more stable than LYO. Overall, almond bagasse powder improves the antioxidant profile and shelf-life of gluten-free bread, highlighting its value as a functional and sustainable ingredient.